ASME 2009 3rd International Conference on Energy Sustainability, Volume 2 2009
DOI: 10.1115/es2009-90298
|View full text |Cite
|
Sign up to set email alerts
|

Economic Potential of Solar Thermal Power Plants With Direct Steam Generation Compared to HTF Plants

Abstract: The direct steam generation (DSG) in parabolic trough collectors is a promising option to improve the mature parabolic trough solar thermal power plant technology of the Solar Energy Generating Systems (SEGS) in California. According to previous studies [1–3], the cost reduction of the DSG process compared to the SEGS technology is expected to be 8 to 25%. All these studies were more or less preliminary since they lacked detailed information on the design of collector fields, absorber tubes required for steam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…239,240 The results from these projects point towards a 8-14% reduction in LCOE compared to SEGS-like plants using synthetic oils as the HTF. 241 Despite the promise of direct steam generation, several engineering challenges, arising due to the twophase flow, need be addressed. These include the higher operating cost due to high pressure required to pump the two-phase mixture.…”
Section: Steammentioning
confidence: 99%
“…239,240 The results from these projects point towards a 8-14% reduction in LCOE compared to SEGS-like plants using synthetic oils as the HTF. 241 Despite the promise of direct steam generation, several engineering challenges, arising due to the twophase flow, need be addressed. These include the higher operating cost due to high pressure required to pump the two-phase mixture.…”
Section: Steammentioning
confidence: 99%
“…This allows the fluid to fully evaporate before exiting the solar field. In a previous analysis, a live steam temperature of 500°C was identified as a viable option within DSG plants . To match the pressure of the indirect steam generation plant considered, the same pressure of 100 bar is considered for the DSG plant.…”
Section: Power Generation Systems' Descriptionmentioning
confidence: 99%
“…Analyses available in the literature have shown that live steam at the exit of DSG fields can reach a temperature of 500°C and a pressure of 120 bar, which leads to a direct increment in the system's overall efficiency, ultimately leading to low cost of energy . The economic potential of DSG‐based PTC plants compared with indirect steam generation PTC plants, which mainly uses synthetic oil as HTF, has been reported in the literature . These studies have concluded that DSG‐based PTC has the potential to reduce the levelized cost of energy up to 11%.…”
Section: Introductionmentioning
confidence: 99%
“…This limits the maximum operation temperature to 400°C and, thus, the overall plant efficiency. Instead, solar thermal power plants based on direct steam generation (DSG) with steam temperatures up to 550°C offer higher efficiencies [1,2]. For further cost reduction cost efficient thermal energy storage (TES) system is required.…”
Section: Dsg Solar Power Plantsmentioning
confidence: 99%